Application of optical techniques in sedimentation study of magnetorheological fluids. (21st November 2021) - Prajapati, Hiren; Lakdawala, Absar
Magnetorheological fluids are colloidal suspensions. They consist of magnetic particles suspended in nonmagnetic carrier fluid. There is large density difference between particles and carrier fluid due to which particle settling takes place. Kynch theory (visual observation) is the most commonly used method to study sedimentation of the colloidal suspensions. However, Kynch theory does not quantify the variation of the particle concentration with respect to time. Therefore, other quantitative methods are applied in recent time by many researchers. In the similar context, we have used UV visual spectroscopy and laser beam deflection methods in sedimentation study of magnetorheological fluids. We observed certain lacuna of the said method in predicting the sedimentation. The results show that, with higher concentration of colloidal suspension, UV-Vis spectroscopy produces hazy results. This is due to presence of micron sized magnetic particles in large amount. Similarly, laser beam deflection method could not predict the concentration of the particles due to the opaque nature of particles. Thus, we propose that caution must be paid before using the UV-Vis spectroscopy and the laser beam deflection method for sedimentation study of magnetorheological fluids.